Partisipasi Orang Kristen di dalam Pemilihan Umum: Studi Kasus Jaringan Marindo pada Pemilu 2014 dan 2019 di Malang Raya, Jawa Timur - Markus Dominggus (Reformed Center for Religion and Society, 2022)
The spacious room provided by the Election Law for popular participation was utilized by Christians in Malang Greater Area in the 2014 and 2019 elections through a collaborative network between individual Christians called Marindo. This study intends to describe the dynamics of such involvement in the typical Indonesian political atmosphere. The thesis it wants to raise is that starting from certain conditions they face in this region, these Christians have adopted a strategy that gives them freedom of movement to mobilize their electoral power. The special contribution of this research to the current findings is the use of non-institutional strategies with all their problems amid Indonesia's electoral democracy climate. On a more theoretical level, it complements other findings about the strategies of minority groups to take part in the democratic process. This research uses a qualitative approach with case study methods and an interpretive lens of theories about the involvement of minority groups in the democratic process.